Effects of multilayer porous ceramics on thermochemical energy conversion and storage efficiency in solar dry reforming of methane reactor. (1st May 2020) - Zhang, Hao; Shuai, Yong; Lougou, Bachirou Guene; Jiang, Boshu; Wang, Fuqiang; Cheng, Ziming; Tan, Heping
Highlights: LTNE model coupled with DRM kinetics determines reactor characteristics. One-layer vs multilayer porous ceramic alters temperature distribution and conversion. Multilayer ceramic could improve reactor thermal efficiency. One-layer ceramic is more reliable for energy storage in most cases. Highly porous 4-layer ceramic could yield efficiency gains of 0.03–2.43%. Abstract: In solar thermochemical systems, the utilization of porous ceramics plays an important role in the enhancement of heat transfer and optimization of reaction conditions, thereby effectively improving the energy conversion and storage efficiency. Compared with the common filling pattern of one-layer porous ceramic (1-LPC), novel changes in the thermal and chemical characteristics can be induced using multilayer porous ceramics (MPCs). To determine whether MPCs have advantages over 1-LPC in solar thermochemical applications, a numerical model was established in this study by combining computational fluid dynamics with dry reforming of methane reaction kinetics. The local thermal non-equilibrium model coupled with the P1 approximation was adopted to solve the solar radiation diffusion and convective heat transfer problems, while the non-Darcy flow effect was considered to predict the momentum dissipation resulting from the porous ceramics. Based on this, the effects of layer number, gap position, porosity, and cell size were investigated to find the optimal application strategies for MPCs. The simulation results indicate that a large temperature gradient in the first gap between two layers of MPCs can usually reduce the wall heat loss and improve the thermal efficiency, but has no universal effect on improving the solar-to-fuel efficiency. Under the current operational conditions, although improvement of the solar-to-fuel efficiency by approximately 0.03%–2.43% can be obtained using a 4-LPC in the cases of high porosities ( ϕ ⩾ 0.86 ) and large mean cell sizes ( d p ⩾ 7 mm ), 1-LPC remains the most reliable filling pattern with a wider range of applications and stable performance.